2003
DOI: 10.1056/nejmoa025142
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Coronary Angioplasty with Fibrinolytic Therapy in Acute Myocardial Infarction

Abstract: A strategy for reperfusion involving the transfer of patients to an invasive-treatment center for primary angioplasty is superior to on-site fibrinolysis, provided that the transfer takes two hours or less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
409
2
28

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,155 publications
(452 citation statements)
references
References 19 publications
10
409
2
28
Order By: Relevance
“…This is also well within the 110 min to 114 min PCI-related delay at which primary PCI is expected to lose its mortality benefit over thrombolytic therapy (13,14). On the other hand, the 110 min estimated PCI-related delay for patients transferred from remote hospitals was longer than in previous randomized clinical trials (3,4). In the present study, DTB times were shorter for patients presenting during normal business hours than for patients presenting during weekends or outside normal duty hours.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is also well within the 110 min to 114 min PCI-related delay at which primary PCI is expected to lose its mortality benefit over thrombolytic therapy (13,14). On the other hand, the 110 min estimated PCI-related delay for patients transferred from remote hospitals was longer than in previous randomized clinical trials (3,4). In the present study, DTB times were shorter for patients presenting during normal business hours than for patients presenting during weekends or outside normal duty hours.…”
Section: Discussionsupporting
confidence: 79%
“…Many studies have shown that transferring STEMI patients is safe, and that the benefits of primary PCI over thrombolytic therapy are conserved when transfer delays are reasonable (2)(3)(4)(5). Based on randomized, controlled trials, the current guidelines for STEMI recommend a door-to-balloon (DTB) time of less than 90 min when performing primary PCI, including transfer time (6)(7)(8).…”
mentioning
confidence: 99%
“…There were delays in many parts of the PCI process. These include the longer catheter door-to-balloon inflation times recorded in our study compared with times achieved in published studies (40 min versus 26 min) (12,14). Another factor was the long average ambulance ride times of 51 min.…”
Section: Discussionmentioning
confidence: 39%
“…Second, ambulance ride time could potentially be improved, however minimally, and probably would not result in a significant decrease in the door-to-balloon time. Third, RCH catheter door-toballoon inflation time could be improved to match that of other studies (12,14), which would result in a 14 min reduction in the door-to-balloon time. Finally, the most significant improvement in the door to balloon time, perhaps by 60 min, could be possible if strategies were implemented to accelerate the assessment, investigation and transfer of STEMI patients in the CGH emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, survivorship bias inherent in our study design may have been introduced because patients who died before arrival at the PCI centre were not included in the PCI databases, thereby falsely lowering mortality in the GEMS group, which had the longest transport times. However, a large Danish study comparing coronary angioplasty with fibrinolytic therapy found that no patients died during transportation to the hospital15, hence we do not consider these two potential sources of bias to be strong enough to have an impact on the overall conclusions.…”
Section: Discussionmentioning
confidence: 99%